KANDUNGAN MINERAL DAN LOGAM BERAT PADA BIOSALT RUMPUT LAUT Padina sp. - Nurdiana Riska; Sri Widodo Agung Suedy; Munifatul Izzati (Jurnal Pro-Life, 2019)
Indonesian is an archipelago that has abundant biological resources, one of which is seaweed. Seaweed is widely used by the community as a standard cake chart, agar and herbal medicinal ingredients. One of the potential of seaweed can produce mineral salts (biosalt). One of the seaweed Biosalt which has not been widely used is from Padina sp. Biosalt Padina sp. contains minerals needed by the human body. The purpose of this study was to determine the amount of salt yield obtained from seaweed Padina sp. and knowing the quality of salt from Padina sp. in terms of the content of macromineral (Ca and Mg), Micromineral (Fe, Mn and Zn) and heavy metals (Cu and Pb). Sampling of Padina sp. Seaweed conducted in Teluk Awur, Jepara. Extraction biosalt Padina sp. carried out at BSF Plant Laboratory, Department of Biology, FSM, UNDIP. Testing with the ICP-OES tool was carried out in the Physical Chemistry laboratory of FMIPA UNNES. Data analysis was descriptive qualitative by comparing the salt content of "biosalt" seaweed with table salt (control). The results showed that the total yield of seaweed biosalt was 9.44 gr / 100 gr or 9.44%. As for that the mineral content of Ca, Mg, Fe, Mn, and Zn in biosalt Padina sp. higher than in table salt. On the other hand, heavy metals Cu and Pb in biosalt Padina sp. lower than table salt. This shows that salt obtained from seaweed Padina sp. safe for humans because they have high mineral content and heavy metal levels which are still below the threshold (<2.0 mg / gr) Keywords: minerals, heavy metals, seaweed, biosalt.